Correlation between estrogen receptor, progesterone receptor, HER-2/neu status and other prognostic factors in carcinoma breast in Indian population - Thiygarajan, Manuneethimaran; Navrathan, Nitesh; T., Mohanapriya; Kumar, Arun; Singh, Balaji (International Surgery Journal, 2016)
Background:Incidence of breast carcinoma (BC) is increasing all over the world. Contrary to the West where it is more common in the elderly; in India it is more common among the younger women. India accounts for nearly six percent of deaths, due to breast cancers in the world and also that one out of every 22 women in India is diagnosed with breast cancer every year. But no information is available on its biological characteristics in the Indian population. Our aim was to evaluate the estrogen receptor, progesterone receptor and HER-2/neu receptor in single institute patients and to compare the expression of these factors with other prognostic parameters such as menopausal state, size of tumor, grade, histological type, mitotic index, lymphovascular invasion and nodal metastases. Methods: This is a prospective study conducted in the Department of General Surgery at Sri Ramachandra Medical University Hospital, Chennai, India. A batch of 60 confirmed patients of BC, diagnosed in between 2012 to 2014, were included in this study. ER, PR and HER-2/neu status were studied by immune-histochemistry and were correlated with other prognostic factors. Results:ER negative and PR negative cases were comparatively high (61.7% and 70%) than the positive cases. 66.7% of the cases were post-menopausal group, 68.3% of cases were T2 tumor and 81.7% cases were ductal carcinoma. There was a significant correlation identified between ER, PR with tumor grade and Mitotic Index of the tumor. HER-2/neu positive cases tended to have significant higher axillary metastasis. There was no significant correlation between ER, PR and HER-2/neu with menopausal state, size, histological type and lymphovascular invasion. Conclusions:The ER, PR and Her2/neu expression in BC in our patients is comparable with the available international data. ER and PR negative expressions are strongly associated with some known bad pathological factors like high grade tumor and high Mitotic Index. HER-2/neu expression was high in advanced diseases like axillary node positive patients.